La crítica de Maimónides a los médicos en El libro del asma (SigMe, 2024)
The treatise that Maimonides dedicated to asthma in 1190, originally titled in Arabic Maqālat fi-l-rabw, was written at the request of a noble patient who suffered from the disease. Thus, the Book of Asthma joins the group of medical works that the Jew from Cordoba wrote on commission, which also includes The Regimen of Health and the Treatise on the Cure of Hemorrhoids. It is a monographic study that was highly cited and admired in the three great cultural worldviews of the Middle Ages, namely Jewish, Muslim, and Christian, due to its rapid translation from Arabic into Hebrew and Latin. It consists of a Prologue and thirteen chapters in which diets and treatments are described. Chapters one to twelve attempt to regulate the patient's life and prevent the disease through indirect means. But in the thirteenth chapter, Maimonides deviates from the specific treatment of asthma and provides a series of recommendations for healing in general, in addition to undertaking a reflection on the ars medica not without criticism of the physicians of his time, whom he accuses of being ignorant for underestimating issues that Hippocrates and Galen had considered difficult. This conception of medicine presented by Rambam is underpinned by philosophical assumptions derived from Hippocratic and Galenic texts, which the Jewish physician notably reinterprets in light of the knowledge of his time.
Keywords: Maimonides, medicine, athsma, soul, physicians.